Politik Dinasti di Negara Demokrasi - Ruri Maydani; M. Faisal Husna; Sri Lili Winarti; Nurhamida Harahap; Ardiansyah Ardiansyah (Jurnal Syntax Admiration, 2024)
Dynastic politic is the biggest challangein building a valuable democracy in a government order. Which the dynastic politic can be seen from the occurrence of a power held by family and kinship group. This phenomenon can be a material for common thoughts, especially the elites and stakeholders by putting forward alternative solution that refer to the rules. In the persvective of democracy, general election and local election are one of the answer that will be able to give birth to people’s desire to get qualified candidates for leaders. The dynasty’s political strategy was used as a tool to secure power by placing family or relative in certain posts in the formal (government) or informal (projects or business) fields. If this continues, the dynastic politic will develop rapidly and the pros contras will emerge in the midst of implementing a government based on Pancasila democracy. this study aims to determine the influence of political dynasties on the development of Pancasila in Indonesia.